1996
DOI: 10.1246/bcsj.69.869
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Photobromination of Fluoroethane. Estimate of the C–H Bond Dissociation Energies and the Heats of Formation of the CH3CHF and CH2CH2F Radicals

Abstract: The gas-phase photobromination of fluoroethane was investigated in the temperature range 80—150 °C in both the presence and absence of chloroethane as an external competitor. The rate constant for α-hydrogen abstraction in CH3CH2F was redetermined relative to that in CH3CH2Cl, and the abstraction of β-hydrogen was measured in the internal competition. The relative rates were combined with the known rate parameters for the bromination of C2H6 to obtain the absolute rate constants (cm3 mol−1 s−1): k(α) = (6.50 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…71 For the fluoroethyl radical, Miyokawa et al 72 reported an experimental ⌬ f H 298°͑ C 2 H 4 F͒ = −14.2Ϯ 2 kcal mol −1 , but the uncertainty in this value is too large for our purposes. The Gurvich tables recommend ⌬ f H 298°͑ C 2 H 4 ͒ = 12.52Ϯ 0.12 kcal mol −1 and ⌬ f H 298°͑ F͒ = 18.97Ϯ 0.07 kcal mol −1 .…”
Section: Barrier and Reaction Enthalpymentioning
confidence: 90%
“…71 For the fluoroethyl radical, Miyokawa et al 72 reported an experimental ⌬ f H 298°͑ C 2 H 4 F͒ = −14.2Ϯ 2 kcal mol −1 , but the uncertainty in this value is too large for our purposes. The Gurvich tables recommend ⌬ f H 298°͑ C 2 H 4 ͒ = 12.52Ϯ 0.12 kcal mol −1 and ⌬ f H 298°͑ F͒ = 18.97Ϯ 0.07 kcal mol −1 .…”
Section: Barrier and Reaction Enthalpymentioning
confidence: 90%
“…Four years later Tschuikow and Salomon studied the photobromation of C 2 H 5 Cl, and analyzing the kinetics and thermochemical data of related compounds they got a somewhat higher value, −74.1 ± 4.6 kJ/mol, for Δ f H 298 ° (CH 3 –CHF). Then, in 1996, an even higher experimental value appeared when Miyokawa et al researched the photobromination of fluoroethane and determined −70.3 ± 8.4 kJ/mol for Δ f H 298 ° (CH 3 –CHF).…”
Section: Resultsmentioning
confidence: 99%
“…Four years later Tschuikow and Salomon 49 studied the photobromation of C 2 H 5 Cl, and analyzing the kinetics and thermochemical data of related compounds they got a somewhat higher value, −74.1 ± 4.6 kJ/ mol, for Δ f H 298 °(CH 3 −CHF). Then, in 1996, an even higher experimental value appeared when Miyokawa et al 47 Chen and his associates 50 using HF/6-31G(d) geometries and frequencies in conjunction with MP2/6-311G(d,p) energies [MP2/6-311G(d,p)//HF/6-31G(d)] determined…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations